LICENSING AND ENFORCEMENTIN MUNICIPAL ENVIRONMENTAL DEPARTMENTS IN THE STATE OF RIO GRANDE DO SUL, BRAZIL - Neto, Gelso Pacheco; Soares, Philipe Ricardo Casemiro; Dalmaso, Cilmar Antonio; Kaineski, Maria Raquel; Milani, Jaçanan Eloisa de Freitas; Almeida, Alexandre Nascimento de (Floresta, 2023)
This study evaluated the environmental departments of some municipalities in Rio Grande do Sul, Brazil, regarding their structure and licensing and enforcement processes. Information was collected through online questionnaires sent to municipalities. The questionnaires addressed the staff, the training of the technical staff and the work structure of the environmental departments in the municipalities. Evaluations and classifications were conducted using the classification tree technique based on municipal data on the environmental licenses issued, and additionally the infraction notices issued as response variables. Thus, it was observed that human resources, effective civil servants and the work team composition are the variables that best explain the issuance behavior of the municipal environmental licenses, and in parts the infraction notices. The other variable that most satisfactorily explains the issuance of infraction notices in the municipalities is the use of their own website with environmental software in the environment departments.